2015
DOI: 10.1016/j.econmod.2015.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Remittance and domestic labor productivity: Evidence from remittance recipient countries

Abstract: For countries with significant labor force like China, India, Bangladesh, Pakistan etc. any longrun growth strategy should focus on augmenting the domestic labor productivity. The advent of globalization and factor mobility has given a recipe to reap up gains from labor abundance for most of the labor abundant countries by strategically converting abundant labor into capital. However, remittance inflow may become counterproductive strategy for growth, if it is viewed within the work-leisure framework. Using he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 62 publications
(57 reference statements)
3
17
0
Order By: Relevance
“…Lucas and Stark's (1985) seminal study indicates that these motivations range from altruism to self interest with various mixes of the two motivations also possible. Frequently, migrant agents send money home to increase the quality of life of their origin families (Al Mamun et al, 2015). They "derive a positive utility from the well-being or consumption level of the famil[ies] left behind" (Piracha and Saraogi, 2011).…”
Section: Related Literaturementioning
confidence: 99%
“…Lucas and Stark's (1985) seminal study indicates that these motivations range from altruism to self interest with various mixes of the two motivations also possible. Frequently, migrant agents send money home to increase the quality of life of their origin families (Al Mamun et al, 2015). They "derive a positive utility from the well-being or consumption level of the famil[ies] left behind" (Piracha and Saraogi, 2011).…”
Section: Related Literaturementioning
confidence: 99%
“…A related paper that directly considers labor productivity is Al Mamun et al (2015). This research nds a positive impact of remittances on labor productivity, in countries that both receive large amounts of remittances and have large labor forces.…”
mentioning
confidence: 92%
“…The literature based on remittance and economic growth shows mixed results ranging from positive to negative and sometimes no relation. Mamun, Sohag, Uddin, & Shahbaz (2015) found that remittance promotes domestic output for the nations with larger remittance inflows and larger workforce but the effect of remittance decreases after a certain level. Imai, Gaiha, Ali, & Kaicker (2014) positively affects to remittance and the volatility of remittance negatively affects economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%